Do Teachers Question the Reality of Pain in Their Students? A Survey Using the Concept of Pain Inventory-Proxy (COPI-Proxy) - Rebecca Fechner; Melanie Noel; Arianne Verhagen; Erin Turbitt; Joshua W. Pate (MDPI AG, 2023)
An assessment of a teacher's concept of their student's pain could be useful to guide preventative and targeted school-based pain science education. We aimed to assess a teacher's own concept of pain against their concept of their student's pain and examine the psychometric properties of the tool. Teachers of 10-12-year-old children were invited to participate in an online survey via social media. We modified the Concept of Pain Inventory (COPI) by inserting a vignette (COPI-Proxy), and we included questions to explore teacher stigma. Overall, a sample of 233 teachers participated in the survey. The COPI-Proxy scores showed that teachers can conceptualize their student's pain separately but are influenced by their own beliefs. Only 76% affirmed the pain in the vignette as real. Teachers used potentially stigmatizing language to describe pain in their survey responses. The COPI-Proxy had acceptable internal consistency (Cronbach's alpha = 0.72) and moderate convergent validity with the COPI (r = 0.56). The results show the potential benefit of the COPI-Proxy for assessing someone's concept of another's pain, particularly for teachers who are important social influencers of children.